Building Intentional Models Using the ERi*c Method - Oliveira, Antonio de Padua Albuquerque; Leite, Julio Cesar Sampaio do Prado (Cadernos do IME - Série Informática, 2011)
Abstract. Requirements elicitation is the backbone of modeling. People aroundthe world do not give very much attention to early requirements elicitation andmore precisely to actors' goals elicitation before eliciting and modelingrequirements. This fault will incur in several losses either during thedevelopment, or worse, later. Goals {flexible (softgoals) and concrete} are thefoundation of GORE and consequently of i*. The ERi*c Method goalelicitation maturity was consolidated by its use in several academic projectsand can support not only to the entire requirements process, but also to reengineer,to change the model of a system, in order to include the use of newtechnology. This paper shows the strength of the ERi*c Method using as anexample a published i* SR model. It also focuses on how the ERi*c Methodcan split an SR model of an Information System into several comprehensiblemodels, applying the concept of SDsituations (Strategic Dependencysituations). Keywords: goals, early requirements, elicitation, modeling, GORE, Goal OrientedRequirements Engineering, ERi*c, goal modeling.